2016
DOI: 10.1155/2016/7924052
|View full text |Cite
|
Sign up to set email alerts
|

Increased Gustatory Response Score in Obesity and Association Levels with IL-6 and Leptin

Abstract: Background. The aim of this study was to investigate the relationship between the circulating IL-6 and leptin levels with taste alteration in young obese patients. Methods. A retrospective case-control study was conducted in thirty obese patients and thirty age- and sex-matched healthy controls. Results. Circulating levels of IL-6 and leptin were significantly increased in obese patients than in controls. However, catalase and ORAC levels were significantly decreased in obese patients compared to controls. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Obese children had a shorter life expectancy by 20 years if they remain obese till young adulthood [ 1 ]. North African Countries and the region of Middle East just like the other developing countries are not spared from the issue of the world [ 2 , 3 ]. Genetics, metabolic, social, cultural and environmental factors interact as different cofactors for the development of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Obese children had a shorter life expectancy by 20 years if they remain obese till young adulthood [ 1 ]. North African Countries and the region of Middle East just like the other developing countries are not spared from the issue of the world [ 2 , 3 ]. Genetics, metabolic, social, cultural and environmental factors interact as different cofactors for the development of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Leptin is primarily secreted by adipocytes, and circulates in lean subjects. Insulin, overfeeding, endotoxins, glucocorticoids, and cytokines increase leptin expression; fasting, testosterone, thyroid hormone, and exposure to cold temperature decrease leptin expression [ 32 34 ]. The leptin receptor (OB-R) activates Janus-activated kinase (JAK), signal transducers and activators of transcription (STAT), insulin receptor substrate, and the mitogen-activated protein kinase (MAPK) pathways [ 35 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…TNF-alfa and IL-6 levels are also significantly higher in obese individuals [ 65 , 66 ], and they correlate with body weight, BMI, waist and hip circumferences, and waist–hip ratio [ 67 ]. It has been shown that obesity-induced low-grade inflammation (raised IL-1, IL-6, and TNF-alfa levels) activates stress kinases, including IKK, JNK, and p38 MAPK, in muscle and fat cells.…”
Section: Immunometabolic Depressionmentioning
confidence: 99%